2020
DOI: 10.14444/7143
|View full text |Cite
|
Sign up to set email alerts
|

Radius of Curvature in Patient-Specific Short Rod Constructs Versus Standard Pre-Bent Rods

Abstract: Background: Recent studies support the need for sagittal alignment restoration when performing lumbar degenerative spinal fusions. The development of patient-specific spine rods (PSSRs) may help maintain or improve sagittal alignment in these surgeries.Methods: A retrospective review was conducted for patients who underwent posterior spinal surgeries involving 4 or less levels. The preplanned PSSR radii of curvature (ROC) was compared with standard prebent rods with a ROC of 125 mm. All surgeries were performe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 18 publications
1
10
0
Order By: Relevance
“…When evaluating PSSRs for degenerative spine cases, the rods were noted to have statistically significant differences in radius of curvature compared to off-the-shelf rods. 13 Further, these differences were similar and consistent from L4-S1 when compared to the upper portion of the lumbar spine (L1-L4). Clinical results, as presented, have also shown improved results over a recently published cohort of degenerative lumbar cases (See Table 4 ).…”
Section: Discussionsupporting
confidence: 56%
“…When evaluating PSSRs for degenerative spine cases, the rods were noted to have statistically significant differences in radius of curvature compared to off-the-shelf rods. 13 Further, these differences were similar and consistent from L4-S1 when compared to the upper portion of the lumbar spine (L1-L4). Clinical results, as presented, have also shown improved results over a recently published cohort of degenerative lumbar cases (See Table 4 ).…”
Section: Discussionsupporting
confidence: 56%
“…Wanivenhaus et al reported that augmented reality-assisted rod bending could reduce surgery time by 20% and increase the accuracy of rod length [20]. Patient-speci c rods were also employed to help achieve satisfactory sagittal alignment, particularly in spine deformity surgery [5,21].…”
Section: Resultsmentioning
confidence: 99%
“…[40,69,212] The spinal cord is just a few mm in diameter and is fairly cylindrical in shape with a Gaussian curvature close to zero. [213,214] Because large amounts of nerve inputs and outputs are processed at the spinal cord, the surface electrode arrays that interface with the tissue are almost always used to stimulate regions of the cord rather than record information. The stimulation tends to be at regions that are damaged with a loss of neuronal bodies, and so electrodes must be able to pass large amounts of current to the spinal cord and are often composed of platinum.…”
Section: Devices For the Cnsmentioning
confidence: 99%